2018
DOI: 10.1038/s41598-018-26226-6
|View full text |Cite
|
Sign up to set email alerts
|

Value of urinary KIM-1 and NGAL combined with serum Cys C for predicting acute kidney injury secondary to decompensated cirrhosis

Abstract: Urinary kidney injury molecule-1 (KIM-1), neutrophil gelatinase-associated lipocalin (NGAL), and serum cystatin C (Cys C) are biomarkers of acute kidney injury (AKI). However, the efficacy of combining these indices to diagnose decompensated cirrhosis is unknown. This study involved 150 patients divided into AKI and non-AKI, and healthy individuals. Urinary KIM-1 and NGAL, serum Cys and creatine, and glomerular filtration rate (GFR) were compared based on Child-Pugh liver function class. Urinary KIM-1 and NGAL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(63 citation statements)
references
References 19 publications
2
56
0
5
Order By: Relevance
“…According to our analysis of changes in renal function‐related indicators within one week after transplantation, we found that both serum and urinary NGAL have the same downward trend as creatinine and β2‐MG, and they have the opposite trend of eGFR, which was consistent with other studies 18‐20 . In the first week after renal transplantation, serum and urinary NGAL, creatinine, and β2‐MG increased, while eGFR decreased.…”
Section: Discussionsupporting
confidence: 89%
“…According to our analysis of changes in renal function‐related indicators within one week after transplantation, we found that both serum and urinary NGAL have the same downward trend as creatinine and β2‐MG, and they have the opposite trend of eGFR, which was consistent with other studies 18‐20 . In the first week after renal transplantation, serum and urinary NGAL, creatinine, and β2‐MG increased, while eGFR decreased.…”
Section: Discussionsupporting
confidence: 89%
“…Upon mild kidney injury, serum CYS-C begins to increase 24–48 h before serum Cr increases, and serum CYS-C gradually increases under disease progression [31]. Previous studies showed that serum CYS-C was an independent and significant indicator for predicting AKI secondary to decompensated cirrhosis [32] and after radical gastrectomy [33]. Previous studies have shown that age, gender, and race can affect the level of serum CYS-C in adolescents [34].…”
Section: Discussionmentioning
confidence: 99%
“…NGAL, also known as lipocalin-2 or ferritin, is a member of the lipocalin superfamily and is produced in response to stress. NGAL may cause acute kidney injury and is one of the most effective biomarkers of acute kidney injury [ 46 ] ( Fig. 4 ).…”
Section: Four Major Hypotheses and Related Biomarkersmentioning
confidence: 99%